A knowledge, attitude and practice (KAP) on dengue among adult population in Felda Sungai Panching Timur, Kuantan, Pahang - Abd. Aziz, Karimah Hanim; Mohd Rus, Razman; Ab Rahman, Jamalludin; Phyu, Htike Myat; Swe, Swe Latt; Nasreen, Hashima E (2015)
With increasing number of dengue cases in Malaysia, it's of utmost importance that immediate action be taken to limit the epidemic. Since dengue control is a behavioral problem, the knowledge, attitude and practice in population needs to be studied in order to control the disease. Hence, the aim of this study is to assess knowledge, attitude and practice regarding dengue and its associated factors among adult residents of Felda Sungai Panching Selatan (SPT), Kuantan, Pahang, 2014.